Internal migration in Northern Ireland: Are people becoming more stuck in place?. Issue 7 (13th May 2020) - Shuttleworth, Ian; Foley, Brian; Champion, Tony
Abstract: The analysis uses the Northern Ireland Longitudinal Study to explore migration trends from 2001 to 2015. Its contributions are to extend this analysis to the period after the 2011 Census, to use administrative data to measure migration not as a transition between places but as (potentially) multiple events over the full 2001–2015 period over different distance bands, to add to the UK evidence base on internal migration trends, and to show how long‐term trends appear to override economic cyclical effects. The results show that internal migration rates over all distance bands fell from 2001 onward, continuing a decline in migration between Super Output Areas recorded since 1981, the first date for which there are data. This indicates that Northern Ireland, despite its unique political and social history, has not been immune to the long‐term migration decline observed elsewhere in Great Britain and other countries such as the United States. The only caveat to this is that when moves from Northern Ireland to other places are included in the long‐distance band of 50 km or more then long‐distance migration returns to near its 2001–2003 level by 2013. The analysis also shows that the same personal characteristics as elsewhere are related to different frequencies and distances of moving.